2020
DOI: 10.1111/jasp.12692
|View full text |Cite
|
Sign up to set email alerts
|

Does the out‐group recognize our mental skills? Cross‐group friendships, extended contact, and the expectation of humanizing perceptions from the out‐group

Abstract: Recent research has shown the negative effect of meta‐dehumanization: the perception that out‐group members deny a fully human status to the in‐group. So far, no strategies have been investigated that allow the improvement of humanity meta‐attributions. In this work, we focused on the two mind perception dimensions: agency (e.g., the capacity of planning actions) and experience (e.g., the capacity of feeling emotions), and investigated whether direct and indirect intergroup friendships are associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Research has shown that common identity can be fueled by a range of factors, like an external threat (Vezzali et al, 2015) or intergroup contact (Capozza et al, 2013). There is evidence that common identity mediates the relationship between and collective action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that common identity can be fueled by a range of factors, like an external threat (Vezzali et al, 2015) or intergroup contact (Capozza et al, 2013). There is evidence that common identity mediates the relationship between and collective action.…”
Section: Discussionmentioning
confidence: 99%
“…On one side, contact literature has provided evidence that common identity predicts more positive attitudes toward the outgroup and more positive feelings toward its members (Gaertner et al, 1994). For instance, Capozza et al (2013) conducted two correlational studies using Italians (Study 1) and Northerners (Study 2) as majority group participants. They found that common identity as Italians was associated with increased empathy and lower anxiety toward immigrants and Southerners, respectively, and in turn, greater humanity attribution.…”
Section: Outgroup Attitudes and Feelingsmentioning
confidence: 99%
“…Promoting workplace friendships and ensuring employee psychological comfort will assist organizations in gaining a competitive advantage by enhancing creativity and, consequently, innovation (Mujerke and Metiu, 2020). Therefore, arranging the workplace culture and environment to support creativity will fully unleash the potential of the workforce (Capozza et al, 2020).…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Once established, workplace friendships provide a climate of trust, intimacy and openness and afford the possibilities for moral learning (Blatterer, 2021). For example, Capozza et al (2020) showed the value of such friendships in combatting biased perceptions and discrimination (p. 524). Similarly, Callagher et al (2021) illustrate how a support network based on camaraderie and professional development helped early career researchers deal with identity threats from discrimination in the field.…”
Section: Theoretical Backgroundmentioning
confidence: 99%